Type catalogue of Terebridae (Mollusca, Gastropoda, Conoidea) in the Natural History Museum, London, U.K. - Salvador, Andreia; Pickering, Joan (Zootaxa, 2017)
The type collection of Terebridae in the Natural History Museum consists of 248 lots. In order to clarify the type status of this material, an annotated alphabetic list by species is provided. The format includes the original citation for each species, type locality, collector, label data, registration number, number of specimens, type status and remarks. Due to the actions of previous workers, fixation of lectotype by inference of holotype is given for 168 species. A bibliography of relevant publications is also provided.